Pengaruh Tingkat Receivable Financing dan Inventory Financing Terhadap Profitabilitas pada Bank Umum Syariah di Indonesia - Lubis, Dinda Silpia; Rukiah; Nasution, Ananda Anugrah (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Abstract Profitability is a ratio that has the objective of knowing how much the ability of the company/banking as a whole is to generate profits over a certain period. Profitability is used as the most appropriate indicator to measure company performance, the higher the profitability, the better the company's performance. The ratio used to measure profitability in this study is ROA. In 2019 and 2020 receivable financing using the qardh contract at PT. Bank Mega Syariah experienced a decline but not accompanied by a decrease in profitability (ROA). Then in 2019 and 2020 inventory financing using a murabaha contract at PT. Bank Aceh Syariah has increased but not accompanied by an increase in profitability (ROA). The formulation of the problem in this study is